Circulating bile acid concentrations and non‐alcoholic fatty liver disease in Guatemala. Issue 2 (28th April 2022) - Rivera‐Andrade, Alvaro; Petrick, Jessica L.; Alvarez, Christian S.; Graubard, Barry I.; Florio, Andrea A.; Kroker‐Lobos, Maria F.; Parisi, Dominick; Freedman, Neal D.; Lazo, Mariana; Guallar, Eliseo; Groopman, John D.; Ramirez‐Zea, Manuel; et al.
Summary: Background: Non‐alcoholic fatty liver disease (NAFLD) is a major liver disease worldwide. Bile acid dysregulation may be a key feature in its pathogenesis and progression. Aims: To characterise the relationship between bile acid levels and NAFLD at the population level Methods: We conducted a cross‐sectional study in Guatemala in 2016 to examine the prevalence of NAFLD. Participants ( n = 415) completed questionnaires, donated blood samples and had a brief medical exam. NAFLD was determined by calculation of the fatty liver index. The levels of 15 circulating bile acids were determined by LC–MS/MS. Adjusted prevalence odds ratios (PORadj ) and 95% CI were calculated to examine the relationships between bile acid levels (in tertiles) and NAFLD. Results: Persons with NAFLD had significantly higher levels of the conjugated primary bile acids glycocholic acid (GCA) (PORadj T3 vs T1 = 1.85), taurocholic acid (TCA) (PORadj T3 vs T1 = 2.45) and taurochenodeoxycholic acid (TCDCA) (PORadj T3 vs T1 = 2.10), as well as significantly higher levels the unconjugated secondary bile acid, deoxycholic acid (DCA) (PORadj T3 vs T1 = 1.78) and its conjugated form, taurodeoxycholic acid (TDCA) (PORadj T3 vs T1 = 1.81). Conclusions: The bile acid levels of persons with and without NAFLD differed significantly. Among persons with NAFLD, higher levels of the conjugated forms of CA (i.e. GCA, TCA) and the secondary bile acids that derive from CA (i.e. DCA, TDCA) may indicate there is hepatic overproduction of CA, which may affect the liver via aberrant signalling mediated by the bile acids. Abstract : Bile acid levels differ between persons with and without NAFLD in Guatemala